Promoting climate-smart agriculture in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
Farmers will have to produce as much food in the next 40 years as they have in the past 8000 to satisfy the needs of the world’s rapidly expanding population. Meeting this challenge will be made all the more difficult by climate change. Even a 2°C rise in temperature by the end of the 21st century will lead to dramatic changes in agricultural productivity and land use. At the Brussels Development Briefing on ‘Climate change, agriculture and food security: proven approaches and new investments’, experts highlighted the policies required to help farmers cope with climate change.